Development of MABBAR Web-Based Evaluation System for Enhancing Arabic Listening Competency (Mahārah al-Istimā’) in Junior High Schools - Fatchiatuzahro; Muhammad Ainul Haq; Ubay Abdillah; Friendis Syani Amrullah; Abdul Fatah (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2026)
The lack of specialized digital tools for structured auditory exposure frequently limits the development of Arabic listening skills (mahārah al-istimā’) at the secondary education level, as observed in preliminary studies at SMP IT Yasalam where conventional audio methods showed limited engagement. This study develops and evaluates the effectiveness of MABBAR, a web-based evaluation system that integrates Native Speaker Text-to-Speech (TTS) and automated feedback to provide self-regulated auditory input. Using a Research and Development (R&D) approach with a modified Borg & Gall model (1983), the study progressed through eight stages from needs analysis to dissemination. The subjects were 39 eighth-grade students at SMP IT Yasalam, Bogor. Data were collected via expert validation rubrics, pre-test/post-test instruments, and a 20-item usability questionnaire using a 5-point Likert scale. The findings indicate that MABBAR is highly feasible, with material experts scoring it 5.00/5.00 and media experts scoring 4.87/5.00. Statistical analysis through a paired-sample t-test revealed a significant improvement in student performance ($p = 0.001$), with the mean score increasing from 74.64 to 84.26. Based on the perception questionnaire, students gave a 96.64% positive response, specifically identifying the benefit of independent audio control in reducing cognitive load. MABBAR transforms the listening evaluation process into an adaptive, self-regulated learning ecosystem suitable for the Society 5.0 era. Keywords: Arabic Linguistics, Arabic Teaching, Mahārah al-Istimā’, MABBAR, Web-based Evaluation.